2017
DOI: 10.3847/1538-4357/aa8d6a
|View full text |Cite
|
Sign up to set email alerts
|

The Magnetic Future of the Sun

Abstract: We analyze space-and ground-based data for the old (7.0 ± 0.3 Gyr) solar analogs 16 Cyg A and B. The stars were observed with the Cosmic Origins UV Spectrographs on the Hubble Space Telescope (HST) on 23 October 2015 and 3 February 2016 respectively, and with the Chandra X-ray Observatory on 7 February 2016. Time-series data in Ca II data are used to place the UV data in context. The UV spectra of 18 Sco (3.7±0.5 Gyr), the Sun (4.6±0.04 Gyr) and α Cen A (5.4 +1.2 −0.2 Gyr), appear remarkably similar, pointing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…For an energy range of 0.3 − 2.5 keV we find log L X = 25.37 and log F X = 2.59 for the QS distribution, a full order of magnitude lower than the 0.1 − 2.4 keV values quoted above. This 0.3 − 2.5 keV QS luminosity is not inconsistent with the very low 16 Cyg B limit of Judge et al (2017). The luminosities inferred from the Schonfeld et al (2017) distributions decrease to log L X = 26.15 − 26.96 in the 0.3 − 2.5 keV range, more consistent with the α Cen AB luminosities quoted by Ayres (2014), which are for 0.2 − 2 keV.…”
Section: Emission Measure Variation With Activitysupporting
confidence: 82%
See 1 more Smart Citation
“…For an energy range of 0.3 − 2.5 keV we find log L X = 25.37 and log F X = 2.59 for the QS distribution, a full order of magnitude lower than the 0.1 − 2.4 keV values quoted above. This 0.3 − 2.5 keV QS luminosity is not inconsistent with the very low 16 Cyg B limit of Judge et al (2017). The luminosities inferred from the Schonfeld et al (2017) distributions decrease to log L X = 26.15 − 26.96 in the 0.3 − 2.5 keV range, more consistent with the α Cen AB luminosities quoted by Ayres (2014), which are for 0.2 − 2 keV.…”
Section: Emission Measure Variation With Activitysupporting
confidence: 82%
“…However, the models of Suzuki (2018) suggest that such stars may end up brighter in X-rays due to much higher coronal densities. Judge et al (2017) recently found a very low upper limit for the X-ray luminosity of 16 Cyg B (G3 V), log L X < 25.5, which is much lower than the minimum QS level of log L X = 26.4 just quoted in the previous paragraph. However, the 16 Cyg observations are Chandra ACIS-I data, which covers an energy range of 0.3 − 2.5 keV, compared to the more traditional 0.1 − 2.4 keV ROSAT/PSPC range that we are using.…”
Section: Emission Measure Variation With Activitymentioning
confidence: 65%
“…Though this result has received some criticism, mainly focusing on selection bias and underestimation of the age uncertainties (Barnes et al 2016), the result has later been confirmed by another independent study (dos Santos et al 2016). Lately, a number of theoretical explanations for the small angular momentum loss of old solar-type stars have also emerged (Metcalfe et al 2016;Brandenburg et al 2017;Metcalfe & van Saders 2017;Judge et al 2017).…”
Section: Introductionmentioning
confidence: 86%
“…In the end, however, after further evolution along the I branch, below a critical Ro −1 , the dynamo may begin to sputter (van Saders et al 2016), the star begins to experience magnetic grand minima (Metcalfe et al 2016), differential rotation weakens (Metcalfe et al 2022) or may even reverse sign (Gastine et al 2014;Karak et al 2020), and the dynamo dies, with P cyc going to infinity (see, e.g., the lengthening P cyc in the evolutionary sequence of G2 stars 18 Sco, the Sun, and α Cen A; Judge et al 2017). With the cycling dynamo shut down, large-scale fields driving spindown vanish, stopping further rotational evolution, and the star evolves vertically off the diagram at constant Ro (e.g., Metcalfe & van Saders 2017, shown by a vertical gold arrow in Figure 18).…”
Section: A New Interpretation Of Dynamo Evolutionmentioning
confidence: 99%